ACL injury risk during Rugby tackle can be evaluate through an on-field task-specific analysis: A pilot study - Pavan, D.; Cibin, F.; Guiotto, A.; Rizzi, A.; Roma, E.; Colangelo, A.; Casagrande, T.; Sgorlon, A.; Sbrocco, G.; Sawacha, Z. (Gait and Posture, 2016)
The physical nature of Rugby Union leads to a high number of contacts and collisions between athletes, which means a higher chance of injury occurring Despite scrums present the highest risk per occurrence, the tackles showed to be responsible for the highest number of injuries and the greatest recovery time. ACL injury has been proved to be one of the major causes of athletes` absence from training sessions and competitions. The second mechanism of ACL injury during a Rugby match have been proved to be a performed tackle. The aim of the present study is to develop an on-field protocol for ACL injury risk screening, during the tackle task. A set of biomechanics parameters that showed to be predictive of ACL injury with different techniques were chosen.